Evaluasi Kejadian dan Indikator Fisis Skala Cuaca Antariksa berdasarkan Variasi Angin Matahari tahun 1963 – 2023 (Evaluation Occurance and Physical Indicators of Space Weather Scale based on Solar Wind Variations in 1963 to 2023) - Herdiwijaya, Dhani (Akademi Angkatan Udara, 2024)
Space weather refers to changes in environmental conditions in near-Earth space as a consequence of the behaviour of the Sun, the nature of the magnetic field of interplanetary space, and the Earth's atmosphere, in particular the magnetosphere and ionosphere layers. The components of space weather are plasma particles, electromagnetic energy and magnetic fields. Solar activity always emits plasma particles into space and creates a plasma stream known as the solar wind. The energetic phenomenon of solar activity comes from solar explosions and corona mass ejections that can cause extreme space weather, namely geomagnetic storms. The intense energy of these storms can damage satellites, disable satellite communications and navigation, disrupt power grids on Earth's surface, and be dangerous to spacecraft. The NOAA (National Oceanographic and Atmospheric Agency) Space Weather Scale, USA was introduced as a way to communicate to the general public about current and future space weather conditions and their possible impacts on humans and space technology systems. The scale is useful for space technology users and those interested in the effects of space weather on spacecraft. The scale describes space environment disturbances for three types of events: geomagnetic storms, solar radiation storms, and radio blackouts. The scale has levels from low to high that are numbered 1 to 5, indicating severity. Each level also lists the likelihood of the impact occurring, the frequency with which the event occurs, and provides a measure of the intensity of the physical cause. The NOAA space weather scale evaluation was conducted for 60 years of solar wind data. Geomagnetic storms with Kp index indicator (N=525960) extreme scale (scale 5) with Kp index of 9 is only 0.11% (N=597). Solar radiation storms with an indicator of proton flux energy> 10 MeV (N = 365015) there are no extreme scale achievements, namely 100 000 particles. The highest flux was 67749 particles (scale 4). Most of the flux (99.85%) was below 1000 proton particles. The extreme radio storm (scale 5), with a solar flare strength of more than X20, has only occurred five times (from 1976 to 2023).